1244. In Vitro Activity of Ceftazidime-Avibactam and Comparator Agents Against MDR Enterobacterales and Pseudomonas aeruginosa Collected in Latin America During the ATLAS Global Surveillance Program 2018-2019. (4th December 2021) - Lob, Sibylle; Hackel, Meredith; Stone, Gregory; Sahm, Daniel F
Abstract: Background: Ceftazidime-avibactam (CAZ-AVI) is a β-lactam/non-β-lactam β-lactamase inhibitor combination that can inhibit class A, C, and some class D β-lactamases. Resistance caused by these β-lactamases often results in multidrug-resistance (MDR). This study evaluated the in vitro activity of CAZ-AVI and comparators against MDR Enterobacterales and Pseudomonas aeruginosa isolates collected from patients in Latin America. Methods: Non-duplicate clinical isolates were collected in 2018-2019 in 10 countries in Latin America. Susceptibility testing was performed using CLSI broth microdilution and interpreted using CLSI 2021 and FDA (tigecycline) breakpoints. MDR was defined as resistant (R) to ≥3 of 7 sentinel drugs: amikacin (AMK), aztreonam (ATM), cefepime (FEP), colistin (CST), levofloxacin (LVX), meropenem (MEM), and piperacillin-tazobactam (TZP). Results: The activity of CAZ-AVI and comparators against all isolates and MDR subsets is shown in the table. MDR rates for the studied species ranged from 16.3% among E. cloacae to 35.7% among K. pneumoniae . CAZ-AVI was active against 98% of Enterobacterales isolates and maintained activity against 74-98% of MDR isolates of the examined Enterobacterales species. Only tigecycline showed higher activity. Among P. aeruginosa, CAZ-AVI was active against 87% of all isolates and 47% of MDR isolates; no other studied drug was more active. The three most common MDR phenotypes among Enterobacterales were 1) R to ATM, FEP, and LVX (n=544, 44.8% of all MDR Enterobacterales; 100% susceptible (S) to CAZ-AVI), 2) R to ATM, FEP, LVX, and TZP (n=150, 12.4% of all MDR Enterobacterales; 99.3% S to CAZ-AVI), and 3) R to all sentinel drugs except AMK and CST (n=145, 11.9% of all MDR isolates; 78.6% S to CAZ-AVI). The three most common MDR phenotypes among P. aeruginosa were 1) R to all sentinel drugs except CST (n=85, 19.7% of all MDR isolates; 24.7% S to CAZ-AVI), 2) R to all sentinel drugs except AMK and CST (n=42, 9.7% of all MDR isolates; 66.7% S to CAZ-AVI), and 3) R to AMK, LVX, and MEM (n=37, 8.6% of all MDR isolates; 24.3% S to CAZ-AVI). Conclusion: These in vitro data suggest that CAZ-AVI can be an effective treatment option for infections caused by MDR Enterobacterales and P. aeruginosa collected in Latin America. Disclosures: Sibylle Lob, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Meredith Hackel, PhD MPH, IHMA (Employee)Pfizer, Inc. (Independent Contractor) Gregory Stone, PhD, AztraZeneca (Shareholder, Former Employee)Pfizer, Inc. (Employee) Daniel F. Sahm, PhD, IHMA (Employee)Pfizer, Inc. (Independent Contractor)